KEANEKARAGAMAN KHAMIR YANG DIISOLASI DARI SUMBER DAYA ALAM PULAU ENGGANO, BENGKULU DAN POTENSINYA SEBAGAI PENDEGRADASI SELULOSA [Diversity of Yeasts Isolated From Natural Resources of Enggano Island, Bengkulu and Its Cellulolytic Potency] - Sumerta, I Nyoman; Kanti, Atit (Research Center for Biology-Indonesian Institute of Sciences, 2016)
The present study revealed the occurrence and diversity of yeasts from natural resources of Enggano Island. The yeasts were isolated from soil, sediment, leaf, leaf litter, fruit, and flower. Isolation was performed using direct plating, membrane filtration, ballistospore-falling and enrichment culture using glucose, xylose and xylan as carbon source. After isolating, yeasts were screened for its cellulolytic potency. The occurrence of yeasts in different isolation technique are clearly found. Most of 87 yeasts isolated, abundant in leaf, soil, and sediment sample. The total yeasts isolated were classified into 32 species based on D1/D2 LSU 26S rDNA sequences analysis which genera of Candida were predominant (33%). The predominant yeast species were identified as Candida tropicalis (16,1%), Cyberlindnera saturnus (16,1%), and Rhodosporidium paludigenum (11,5%). Screening on carboxymethyl cellulose medium, there are 43 isolates within 22 yeasts species have cellulolytic activity. Four species of Basidiomycetous have high activity which includes Pseudozyma antartica Y15Eg001; Pseudozyma hubeiensis Y15Eg015; Anthracocystis chrysopogonis Y15Eg072; Cryptococcus laurentii Y15Eg017 and two from Ascomycetous are Sarocladium bactrocephalum Y15Eg226, Y15Eg227. Some of cellulolytic yeast isolates are indicated as new species candidate and required to reconfirm in another conserve regions to ensure its taxonomic position. Various yeasts isolated from Enggano Island with its cellulolytic potency should contribute to scientific information regarding microbial genetic resources of outer islands of Indonesia.